Monitoring training load, recovery, and performance of Brazilian professional volleyball players during a season - Debien, P. B.; Mancini, M.; Coimbra, D. R.; de Freitas, G. S.; Miranda, R.; Bara Filho, M. G. (International Journal of Sports Physiology and Performance, 2018)
Purpose: To describe and analyze the distribution of internal training load (ITL), recovery, and physical performance of professional volleyball players throughout 1 season. Methods: Fifteen male professional Brazilian volleyball players participated in this study. The session rating of perceived exertion (s-RPE) and Total Quality Recovery (TQR) score were collected daily for 36 wk. s-RPE was collected after each training session, and TQR, before the first session of the day. The sum of the ITL of each session during the week, training monotony, strain, acute:chronic workload ratio, match difficulty score, and average of the TQR scores were recorded for the analysis. In addition, the athletes performed countermovement-jump (CMJ) tests with and without the use of the arms 4 times over the season. Results: The season mean weekly ITL was 3733 (1228) AU and the TQR was 15.02 (0.71). The ITL and recovery demonstrated undulating dynamics over the 36 wk, with higher weekly ITL in the preparatory periods (F=50.32; P<.001) and worse recovery during the main competition (F=6.47; P=.004). Negative correlations were found between TQR and ITL variables (P<.05). There was improvement and maintenance in CMJ tests without (F=11.88; P=.001) and with (F=16.02; P<.001) the use of the arms after the preparatory periods. Conclusions: The ITL variables, recovery, and physical performance changed significantly throughout a professional volleyball season. Despite the decrease in ITL during the main competitive period, the correct distribution of weekly ITL seems to be very important to guarantee the best recovery of athletes.